Antibiotic Fermentation Broth Treatment by a pilot upflow anaerobic sludge bed reactor and kinetic modeling - Coskun, T.; Kabuk, Ha.; Varinca, K. B.; Debik, E.; Durak, I.; Kavurt, C. (ELSEVIER SCI LTD, 2012)
In this study, an upflow anaerobic sludge blanket (UASB) mesophilic reactor was used to remove antibiotic fermentation broth wastewater. The hydraulic retention time was held constant at 13.3 days. The volumetric organic loading value increased from 0.33 to 7.43 kg(COD) m(-3) d(-1) using antibiotic fermentation broth wastewater gradually diluted with various ratios of domestic wastewater. A COD removal efficiency of 95.7% was obtained with a maximum yield of 3,700 L d(-1) methane gas production. The results of the study were interpreted using the modified Stover-Kincannon, first-order, substrate mass balance and Van der Meer and Heertjes kinetic models. The obtained kinetic coefficients showed that antibiotic fermentation broth wastewater can be successfully treated using a UASB reactor while taking COD removal and methane production into account. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Anaerobic treatment; Antibiotic fermentation broth wastewater; Kinetic model; UASB; PHARMACEUTICAL WASTE-WATER; BLANKET UASB; PERFORMANCE; REMOVAL; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels